Oligosecretory multiple myeloma: a devastating presentation of a difficult diagnosis. Issue 4 (22nd April 2021) - Roque, Ricardo; Machado, Laura; Flor, Duarte; Cunha, Francisca
Abstract : A 57-year-old man with lumbar pain and fever was diagnosed with spondylodiscitis. Afterward, he acquired full paraplegia. Image studies showed a mass extending from D9 to the vertebral canal, plus numerous adjacent osteolytic lesions. Serum immunoelectrophoresis was normal, bone marrow had 0.5% of monoclonal plasmocytes, but D9's biopsy found a plasmacytoma. Despite bone marrow aspiration results, skeleton osteolytic lesions made multiple myeloma (MM) a more plausible diagnosis, later confirmed by the biopsy. The absence of classical MM findings, alongside a medullary compression syndrome, suggested an oligosecretory MM, which was proved by an altered FLC essay. This delayed diagnosis, with multiple diagnostic misguiding leads, also presents rare IgA and lambda chains production and normal levels of uninvolved immunoglobulins. Oligosecretory MM can lead to an inaccurate and delayed diagnosis, with devastating consequences to patient's morbidity and mortality. Therefore, FLC essay is essential in early assessment of potential MM patients.